THE CONSUMPTION OF ORGANIC RICE IN THE HOUSEHOLD LEVEL AT SLEMAN REGENCY - Failla Rhomtika Damayanti; Jangkung Handoyo Mulyo; Any Suryantini (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2013)
The purpose of this study: 1) how does the organic rice consumer behavior at the houshehold level in Sleman Regency? 2) How do the characteristic of consumed organic rice? 3) ehat are the factors that influence the amount of organic rice consumption at the household level in SLeman Regency?The respondents were households that consume organic rice and live in Sleman Regency. In order to know organic rice consumer behavior, the variable that observed include. The decision makers, the main reason, place of purchase, intencity, amount, and the percentage of organic rice consumption. The characteristics of organic rice determined from varieties and brands of consumed organic rice. To determine the factors that influence the amount of organic rice consumption the tested variables were education level, organic rice prices, the price of substitute goods, family size, income, the price of complementary goods, and the main reason to consume organic rice.Results of this research indicate, 1) decision-making in organic rice consumption is determined by the wife (92,5%), the main source of information comes from the electronics media (32.2%), the main reason of organic rice consumption is the health factor (80%), most consumers choose distributor as a polace to purchase organic rice, the main reason is good service (35%), organic rice consumption intensity is continuously (67,5%) and the amount of consumption pe month is 10-20 kg, 2) consumers of organic rice in Sleman mostly (22,5%) consume organic rice from pandan wangi variety with JOL brands that have a characteristic of dull white color, rice washing color level is quite clear, fragrant rice aroma, rough texture, low broken rice percentage, slightly sweet taste, high fluffer level and more durable resistance (not perishable) 3) factors that positively affect organic rice consumption are the number of family members, the price of non-organic rice, corn prices and negatively by price of organic rice.